2017
DOI: 10.1016/j.adro.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 trial of preoperative image guided intensity modulated proton radiation therapy with simultaneously integrated boost to the high risk margin for retroperitoneal sarcomas

Abstract: PurposeTo conduct phase 1 and 2 trials with photon intensity modulated radiation therapy and intensity modulated proton therapy (IMPT) arms to selectively escalate the retroperitoneal sarcoma preoperative radiation dose to tumor volume (clinical target volume [CTV] 2) that is judged to be at a high risk for positive margins and aim to reduce local recurrence. We report on the IMPT study arm in phase 1.Methods and materialsPatients aged ≥18 years with primary or locally recurrent retroperitoneal sarcoma were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 35 publications
2
39
1
1
Order By: Relevance
“…Progress in the technology associated with various perioperative RT modalities has strengthened their potential in the surgical treatment of axial STS, especially along with margin setting. 22,23 However, for cases of unresectable axial STSs, there are still not enough data concerning the efficacy of each of the modalities. At this stage, CIRT could be a treatment option for unresectable localized axial STSs.…”
Section: F I G U R E 3 Overall Survival In Patients With Metastasesmentioning
confidence: 99%
“…Progress in the technology associated with various perioperative RT modalities has strengthened their potential in the surgical treatment of axial STS, especially along with margin setting. 22,23 However, for cases of unresectable axial STSs, there are still not enough data concerning the efficacy of each of the modalities. At this stage, CIRT could be a treatment option for unresectable localized axial STSs.…”
Section: F I G U R E 3 Overall Survival In Patients With Metastasesmentioning
confidence: 99%
“…In a case series by Yoon et al (2010) preoperative proton-beam radiation therapy in RPS was shown to allow marked sparing of OARs in comparison to IMRT [44]. In a prospective, phase 1 clinical trial of preoperative intensity modulated proton therapy for RPS, a dose escalation to 63 GyE was achieved with only mild acute toxicities and one late grade-3 hydronephrosis [45]. However, results of a parallel phase 1 study of the IMRT have not yet been published.…”
Section: Discussionmentioning
confidence: 99%
“…This is typically the region of tumor abutting the posterior abdominal wall, vertebral bodies, and great vessels. Early reports for this technique are encouraging, but further data for both safety and efficacy are warranted before this approach can become standard practice . Mature results of a Massachusetts General Hospital‐led multi‐center Phase I‐II trial of proton and photon dose escalation are eagerly awaited .…”
Section: Introductionmentioning
confidence: 99%
“…Intensity modulated protons (IMPT) achieves dose conformality comparable to that of IMRT but with the additional benefit of a lower integral dose . As noted above, the ability to selectively increase the radiation dose with either IMRT or IMPT offers the attractive possibility of dose escalation to selected areas of the target such as the posterior abdominal wall, aorta, and vertebral bodies where it may be hardest to achieve an adequate surgical margin …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation